AB0179 Serum levels of interleukin-33 are associated with depressive symptoms in patients with primary sjÖgren's syndrome. (12th June 2018) - Li, Z.; Fu, T.; Dong, C.; Li, L.; Gu, Z.
Abstract : Background: Primary Sjögren's syndrome (pSS) is a systemic autoimmune disease which is more common among women than men. Extraglandular manifestations are commonly reported, including central nervous system (CNS) involvement such as headaches, cognitive deficits and mood disorder. Among mood disorder, depression is one of the most frequent disorders observed in patients with pSS. The pathogenesis of depression in pSS remains unclear. Objectives: The aim of this study was to explore potential relationships between serum interleukin-33 (IL-33) levels and depressive symptoms in primary Sjögren's syndrome (pSS) patients. Methods: We included 116 consecutive pSS patients (36 depression patients), and 71 (18 depression patients) age-and sex-matched healthy controls. The presence of depressive symptoms was determined through the Hospital Depression Scale (HDS). IL-33 levels were measured by enzyme-linked immunosorbent assay (ELASA) using commercial kits. Results: There was no significant difference between pSS patients and controls. But, in pSS patients, the serum IL-33 levels were significantly lower in depression patients as compared to patients without depression [40.18 (IQR, 31.79–66.70) ng/ml vs. 39.95(IQR, 121.73)ng/ml; Z=−3.029, p=0.002]. A direct negative correlation between the score of HDAS-D and sera IL-33 levels (r=−0.805, p=0.000) in pSS was also observed. In logistic regression model using depression as the dependent variables, IL-33 is the independent predictors of depression in pSS (β=0.004; OR=1.004; 95% CI:1.998–0.011; p=0.170). Surprisingly, sera IL-33 levels were lower in depression patients with pSS compared to depression patients without pSS (Z=−2.316, p=0.021). Conclusions: Conclusion: In pSS, IL-33 is the independent predictors of depressive disorders. Serum IL-33 levels are decreased in pSS patients with depressive symptoms, suggesting that IL-33 may play a unique role in depression with pSS. Acknowledgements: This study was funded by the Chinese National Natural Science Foundation (Grant no. 81671616, and 81471603); Jiangsu Provincial Commission of Health and Family Planning Foundation (Grant no. H201317 and H201623); Science Foundation of Nantong City (Grant no. MS32015021, MS2201564, MS22016028 and MS22016019); Science and Technology Foundation of Nantong City (Grant no. HS2014071 and HS2016003). Disclosure of Interest: None declared